IMPACT OF PRADHAN MANTRI JAN DHAN YOJANA PROGRAM ON ACCESS TO CREDIT - Shah, Neeraj (Indian Journal of Finance and Banking, 2023)
This research paper investigates the impacts of the Pradhan Mantri Jan Dhan Yojana (PMJDY) program on access to credit for individuals living below the poverty line in India since its inception in 2014. The PMJDY initiative aims to enhance financial inclusion and alleviate poverty by providing banking services and credit access to marginalized populations. The paper begins with a comprehensive literature review, tracing the historical context of financial inclusion in India, the evolution of policies, and previous research on the subject. It then delves into the PMJDY program’s features, implementation, and progress, highlighting its efforts to offer zero-balance accounts and overdraft facilities. The paper employs regression analyses, both at the national and district levels, to examine the relationship between various factors, such as GDP per capita, population density, literacy rates, and PMJDY adoption. These analyses had shed light on the success of the PMJDY program in advancing financial inclusion throughout different regional dynamics. The findings provide insights into the program’s effectiveness in improving credit access for the economically disadvantaged. Ultimately, this research contributes to the ongoing discourse on financial inclusion and informs policymakers on strategies to combat poverty and foster inclusive economic growth especially with policies relating to credit access. JEL Classification Codes: C00, B21, G18, G53.